Inability of p53-reactivating compounds Nutlin-3 and RITA to overcome p53 resistance in tumor cells deficient for p53Ser46 phosphorylation - Teng, Ma; Yamada, Shumpei; Ichwan, Solachuddin J. A.; Ohtani, Kiyoshi; Otsu, Megumi; Ikeda, Masa-Aki (ELSEVIER, 2012)
The p53 tumor suppressor protein plays key roles in protecting cells from tumorigenesis. Phosphorylation of p53 at Ser46 (p53Ser46) is considered to be a crucial modification regulating p53- mediated apoptosis. Because the activity of p53 is impaired in most human cancers, restoration of wild-type p53 (wt-p53) function by its gene transfer or by p53-reactivating small molecules has been extensively investigated. The p53-reactivating compounds Nutlin-3 and RITA activate p53 without genotoxic stress by antagonizing the action of its negative regulator Mdm2. Although controversial, Nutlin-3 was shown to induce p53-mediated apoptosis in a manner independent of p53 phosphorylation. Recently, RITA was shown to induce apoptosis by promoting p53Ser46 phosphorylation. Here we examined whether Nutlin-3 and RITA can overcome resistance to p53- mediated apoptosis in p53-resistant tumor cell lines lacking the ability to phosphorylate p53Ser46. We show that Nutlin-3 did not rescue the apoptotic defect of a Ser46 phosphorylation-defective p53 mutant in p53-sensitive tumor cells, and that RITA neither restored p53Ser46 phosphorylation nor induced apoptosis in p53Ser46 phosphorylation-deficient cells retaining wt-p53. Furthermore, treatment of Nutlin-3 or RITA, together with adenoviral p53 gene transfer, also failed to induce apoptosis in p53Ser46 phosphorylation-deficient cells either expressing or lacking wt-p53. These results indicate that Nutlin-3 and RITA are unable to induce p53-mediated apoptosis in the absence of p53Ser46 phosphorylation. Thus, the dysregulation of this phosphorylation in tumor cells may be a critical factor that limits the efficacy of these p53-based cancer therapies.